Differentiating Pyogenic Brain Abscesses and Tuberculous using Magnetization Transfer MR Imaging and in Vivo Proton MR Spectroscopy - Zia Ul Islam, Sumera Nighat, Atqa Firdous, Hammad Ahmad Saqib, Umaima Majeed, Mahwish Zahra (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find whether in vivo proton MR spectroscopy and magnetization transfer (MT) MR imaging can be used to differentiate between tuberculous brain abscess and pyogenic brain abscess. Study Design: Retrospective Place and duration: Radiology Department of Ibn_e_Sina Hospital Multan from January 2021 to January 2022. Methodology: The study included 15 subjects with brain abscesses who underwent in vivo MR spectroscopy, MT MR imaging and conventional MR imaging. Those with other systemic diseases were excluded. These techniques were also performed on 10 sex and age-matched control subjects for comparing MT ratios in normal and diseased parenchymal locations. 13 tuberculous abscesses were found in 4 patients, and 20 pyogenic abscesses were found in 11 patients. MT MR imaging and in vivo MR spectroscopy were used to evaluate suspected brain abscesses. Results: The mean MT ratio of the pyogenic brain abscesses was 25.55±1.60.MR spectroscopy showed that in pyogenic abscesses level of amino acids (valine, isoleucine, leucine) was 0.8 ppm and lipid and lactate was 1.2 ppm. Additionally, acetate, 1.91 ppm; glycine, 3.55 ppm; succinate,2.40 ppm and alanine, 1.47 pm were also seen. Four patients had 13 tuberculous abscesses. The mean MT ratio obtained from tuberculous abscesses was 19.87±1.54, which was significantly lower compared to the cortical grey matter, deep grey matter, white matter and pyogenic abscess (p<.001). Conclusion: MT ratios in tuberculous brain abscesses were lower than in pyogenic abscesses. In vivo, MR spectroscopy in pyogenic abscesses did not show amino acids. Tuberculous brain abscess can be differentiated from the pyogenic abscess by using both in vivo MR spectroscopy and MT MR imaging. Keywords: Pyogenic brain abscess, tuberculous brain abscess, MR spectroscopy